Primary urachal signet ring cell carcinoma: A case report - Wang, Qing; Chen, Xiaolong; Zhang, Jianqing; Luo, Yuting; Jiang, Kehua (Frontiers in Oncology, 2022)
Urachal signet ring cell carcinoma is a kind of rare but aggressive tumor, and a few cases have been reported previously. A 49-year-old male patient with primary complaints of increased frequency of urination, urodynia, and hematuria was diagnosed to have primary urachal signet ring cell carcinoma by our department. Multiple metastases were found in the sigmoid colon, terminal ileum, mesentery, and peritoneum during the operation, and palliative surgery involving partial cystectomy with en bloc resection of the urachus was then performed. A chemotherapy regimen of fluorouracil combined with cisplatin was made for this case. In addition, this patient also received anlotinib for targeted therapy. So far, this patient has done well on regular follow-up for 6 months and is in stable condition. We reported this additional urachal signet ring cell carcinoma case and conducted a literature review to strengthen our cognition of this disease.